CO2 capture in pilot-scale unit using solid adsorbent in biomass fluidised bed boiler flue gas - Michael Dvořák; Jan Hrdlička; Lukáš Pilař; Pavel Skopec; Jiří Burda (Acta Polytechnica)
The search for methods to capture carbon dioxide (CO2) emissions from solid fuel combustion processes has led to the development and subsequent testing of alternative innovative CO2 capture technologies. Vacuum Pressure Swing Adsorption (VPSA) method is a promising technology for efficient CO2 capture using solid sorbents. This article introduces CO2 capture using the VPSA technology, providing description of the selected VPSA method and the construction of a pilot-scale unit for VPSA CO2 capture. The main goal of this article is to present experimental results, including a description of the pilot-scale unit used for the VPSA adsorption tests using zeolite 13X, an industrially proven sorbent for CO2 capture. The measured adsorption values were compared with theoretical isotherms, allowing the assessment of VPSA method efficiency and accuracy in practical conditions. Results indicated discrepancies between the experimental unit and the theoretical adsorption models, attributed to non-ideal conditions, non-optimised processes, incomplete drying of the sorbent, and temperature variations affecting the adsorption efficiency. The conclusion confirms the VPSA lab unit’s ability to adsorb CO2 using solid sorbents, suggesting that further research and additional tests with new alternative sorbents is needed.